Effects of land use and sampling distance on water quality in tropical headwater springs (Pimenta creek, São Paulo State, Brazil) - Ferreira Marmontel, Caio Vinicius [UNESP]; Lucas-Borja, Manuel Esteban; Rodrigues, Valdemir Antonio [UNESP]; Zema, Demetrio Antonio (Elsevier, 2018)
The studies targeted to hydrology and water quality are scarce in tropical headwater streams. In these delicate ecosystems the comprehension of water quality can constitute a challenge, because the impact of land uses on stream dynamics is particularly severe in tropical areas. To fill this gap, an evaluation of water quality in a headwater streams (Pimenta creek, São Paulo State, Brazil) under tropical conditions was performed. The implementation of linear mixed models to water quality parameters allowed to know how and to what extent water flowing in these headwaters are influenced by: (i) the spatial variation of spring locations; (ii) the different land uses; and (iii) the state of conservation of the riparian vegetation. Both the land uses in the surroundings of water springs (native forest, degraded vegetation, agriculture and pasture) and the sampling points (exactly in the spring and 10, 30 and 50 m downstream) were found to be factors able to explain water quality variability. Most of the analysed parameters, some of which strongly correlated each others (mainly electrical conductivity, Total Dissolved Solids and salinity, but also color, turbidity and iron concentrations), showed significant variations mainly due to the effects of the different land uses, but also to the distance from water spring. The instability of the water quality parameters in springs degraded from its headwater was also demonstrated. The water springs with developed riparian vegetation of natural forest (in a preserved or even disturbed conservation level) showed the best conditions in the aquatic environment (lower temperature, turbidity, color, nitrite and nitrate concentrations, neutral pH). Conversely, in the water springs with pasture or agricultural activities a general worsening of water quality was detected (worse turbidity, color, pH, nitrate and nitrate concentrations). Overall, the study has confirmed how much aquatic environment is sensitive to changes in the environment.
Keywords: Land use; Linear mixed model; Pasture; Riparian vegetation; Tropical forest; Water spring